The Relationship between Management Skills and Financial Management Proficiency in MSMEs - Dian Harmonia; Selvi Agustina (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research aims to investigate the relationship between management skills and financial management proficiency within Micro, Small, and Medium Enterprises (MSMEs). Employing a qualitative research design, the study utilizes purposive sampling to select participants from diverse MSMEs. Data collection techniques include in-depth interviews and document analysis. Thematic analysis is employed to analyze the gathered data. Preliminary findings suggest a nuanced interplay between management skills and financial management proficiency, highlighting the significance of managerial acumen in navigating financial challenges within MSMEs. This study contributes to the understanding of how effective management practices influence financial decision-making and overall business sustainability in the MSME sector